Pre-Exposure Prophylaxis Knowledge, Perceptions, and Experiences Among Rural Gay, Bisexual, and Other Men Who Have Sex With Men in the Northeastern United States - D'Arcangelo, Noah A. (Tufts Archival Research Center, 2021)
A qualitative study that seeks to better understand the unique perspectives and lived experiences of gay, bisexual, and other men who have sex with men who live in rural areas of the northeastern United States related to Pre-Exposure Prophylaxis (PrEP).; Thesis (B.A.)--Tufts University, 2021.; Submitted to the Dept. of Community Health.; Committee: Madina Agénor, ScD, MPH; Alecia McGregor, PhD.